(untitled) (Chichester, 1997)
German Limited Liability Company Edited is the most common business form in Germany - over 600,000 GmbH companies compared with just 3,000 stock corporation companies. To run a successful operation in Germany, foreign investors must understand the GmbH.Recognising this need, the authors of German Limited Liability Company have drawn on years of experience advising domestic and international clients to produce a practical and comprehensive guide.
Keywords: Private companies,Corporation law,Công ty tư nhân,Luật tổng công ty; Law and legislation,Luật và pháp luật; Germany,Germany,Nước Đức,Nước Đức